2022
DOI: 10.1097/eja.0000000000001672
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of COVID-19 and seasonal influenza mortality and outcomes in the ICUs of a French university hospital

Abstract: BACKGROUND SARS-Cov-2 (COVID-19) has become a major worldwide health concern since its appearance in China at the end of 2019.OBJECTIVE To evaluate the intrinsic mortality and burden of COVID-19 and seasonal influenza pneumonia in ICUs in the city of Lyon, France.DESIGN A retrospective study.SETTING Six ICUs in a single institution in Lyon, France.PATIENTS Consecutive patients admitted to an ICU with SARS-CoV-2 pneumonia from 27 February to 4 April 2020 (COVID-19 group) and seasonal influenza pneumonia from 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Conversely, in a recent French study, De Marignan et al . [ 38 ] reported that COVID-19 patients had higher 90-day adjusted mortality in the ICU than influenza patients. However, the authors did not include patients hospitalised during the 2009 A H1N1 pandemic, a particularly severe form of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a recent French study, De Marignan et al . [ 38 ] reported that COVID-19 patients had higher 90-day adjusted mortality in the ICU than influenza patients. However, the authors did not include patients hospitalised during the 2009 A H1N1 pandemic, a particularly severe form of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up was completed on June 4, 2020 for the 4 groups. The patients in the COVID-19 and influenza groups were originally included in a previous study by our group 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Microsoft Inc., Redmond, W.A, USA). The methods for data collection and quality control have been previously described 9 . Methods used for detection of the 4 different viruses are detailed in the supplementary information.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the pre-omicron group were younger and had fewer comorbidities than those in the remaining groups, consistent with the results of studies conducted during the initial stages of the pandemic. 11 12 13 14 15 16 Conversely, the baseline characteristics were similar between the omicron and influenza groups, with almost half of the patients aged ≥ 70 years and a high prevalence of comorbidities. The age distribution and prevalence of comorbidities varied among patients with the omicron variant and those with previous COVID-19 variants.…”
Section: Dicussionmentioning
confidence: 98%
“…However, such studies were conducted during the early stages of the pandemic when effective treatment strategies had not yet been developed, which limits the generalizability of the findings. 11 12 13 14 15 16 Therefore, an updated evaluation of this topic is required.…”
Section: Introductionmentioning
confidence: 99%